The economic potential of industrial parks in the Northern Great Plain Region - Papdi, József Ákos (Acta Agraria Debreceniensis, 2009)
The practice of the conception and park-like economic development (between market economy circumstances) seems to be novel in our country. The first industrial parks have been established decentralized, with a local initiation, with some determining foreign undertakings early in the 90 years. Since then the increase of the number of the parks is high also the areas which have weaker economic level. We have make attention (in the development politics) to the industrial parks working in the most harmful micro-regions, where the capital task is to extension of the employment, and to involvement of the capital. In the Northern Great Plain Region there are 31 industrial park at the ends of 2007. There are developed infrastructure and service in the big part of the parks. The smaller part of the parks cannot live on its title of industrial park, because of regional position, and concerned their management troubles. But the extension and developing of the park’s economic is very important in the region.